Strengthening Police Ethics by Optimizing the Ethics Commission's Role as Guardian of Good Governance Principles - Annisa Erikha; Riswadi Riswadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The code of ethics is an essential instrument in maintaining professionalism, integrity, and accountability within an institution, including the Indonesian National Police (Polri). As part of the effort to enforce ethical standards within the police force, the Police Code of Ethics Commission (KKEP) plays a role in ensuring that each police officer performs their duties in accordance with applicable legal and moral norms. The role of the KKEP becomes highly relevant in the context of good governance, where the principles of transparency, accountability, and the supremacy of law must be the primary foundations of government administration, including within the police system. This study conducts a normative juridical analysis of the role of the Police Code of Ethics Commission in realizing good governance within Polri. A normative juridical approach is used to examine the legal aspects regulating the authority and working mechanisms of the KKEP, by reviewing various regulations, such as the Chief of Police Regulation on the Police Profession Code of Ethics, as well as other legal documents. Additionally, this research also refers to the concept of good governance developed in the study of administrative law and public policy. Through this research method, the study will discuss how the structure and authority of the KKEP are designed to uphold police ethics, as well as how the implementation of the code of ethics can contribute to increasing public trust in the police institution. Therefore, this study is expected to provide a deeper understanding of the position and strategic role of the KKEP in ensuring the professionalism and integrity of Polri members in supporting the principles of good governance in Indonesia.